Evaluation of Performance Perceptions in Adult Combat Athletes about Rapid Weight Loss Practices and Poor Eating Habits in Two Lebanese Cities – A Pilot Study - Haider Mannan; Melissa El Boustany; Krystel Kfoury; Yonna Sacre (Universitas Negeri Semarang, 2024)
Background: Combat sports are competitive contact sports where two participants (one-on-one conflicts) battle. Rapid weight loss (RWL) with dehydration (a dangerous practice) followed by rapid weight gain (RWG) is a standard pre-competition protocol. To achieve pre-competition weight limits, combat athletes often use rapid weight loss techniques that, in addition to an unhealthy diet, play an essential role in their physical performance. Objective: This pilot study assessed the impact of these two factors on the perceived performance of combat athletes, such as speed, endurance, fitness, and more, in two Lebanese cities. Methods: We selected a group of 384 combat athletes aged 18-40 from 65 private clubs in Beirut and Mount Lebanon. All completed questionnaires about socio-demographics, BMI, rapid weight loss practices, diet, and perceived performance. Findings: Combat athletes who adopted adequate rapid weight loss practices were positively associated with a healthy diet (polycorrelation = 0.1894, SE = 0.0745, Wald chi-square statistic = 6.46320, p<0.0001). Also, adequate rapid weight loss (polycorrelation = 0.9667, SE = 0.0083, Wald's chi-squared statistics = 13565.23, p<0.0001) and healthy diet (polycorrelation = 0.3393, SE = 0.0700, Wald's chi-square statistics = 23.4948, p<0.0001) were positively associated with compatible perceived performance. Recommendation: There is a link between rapid weight loss practices, poor eating habits, and perceived performance. Rapid weight loss practices can prevent combat athletes from getting the nutrients they need, which can interfere with their performance, damage their immune system, and increase the risk of injury. Large-scale longitudinal studies are required to confirm the findings.